Análisis de falla en separadores de gas de las bombas electrosumergibles (esp) en los pozos petroleros (2019)
A failure analysis is performed on an intake of the ESP. Historically there have been 4 failures with the same piece, so it is necessary to perform a thorough analysis to find the root cause of the failure and avoid future mechanical failures with the piece